A clinical decision support system to increase appropriateness of diagnostic imaging prescriptions. (1st September 2018) - Calcaterra, Domenico; Di Modica, Giuseppe; Tomarchio, Orazio; Romeo, Placido
Abstract: The use of diagnostic imaging procedures has significantly risen in the last decade. However, several studies estimate that a substantial number of requests for diagnostic imaging are inappropriate, leading to unnecessary exposure to radiation, increased wait times, and ineffective use of health care resources. Although many radiology societies from all over the world have published imaging referral guidelines which general practitioners should follow when ordering imaging examinations, the uptake by practitioners is still far from being considered realized nor are the guidelines well integrated in the clinical workflows. In this paper we present a Clinical Decision Support System (CDSS) that provides physicians with real-time guidance to prescribe patients appropriate diagnostic imaging tests. The CDDS embeds the imaging referral guidelines in the form of coded rules that help the physicians in their prescription work. It also provides tools that promote the collaboration among physicians and radiologists in the diagnostic process. The work has been carried out in a recently ended research project which investigated the phenomenon of inappropriate imaging prescribing in Sicily, Italy. Results from a field experimentation show a high potential impact of the CDSS in reducing inappropriate imaging.